THE RELATIONSHIP BETWEEN THE IMPLEMENTATION OF TUTORING AND STUDENTS' LEARNING MOTIVATION AT GRADE V SDN 03 MARGOYOSO - Nor Laila Safitri; Henry Suryo Buntoro; Ratri Rahayu (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Tutoring institutions are a form of nonformal education aimed at helping students adapt to academic, social, and psychological demands. This study aimed to examine the implementation of tutoring for fifth-grade students at SD N 03 Margoyoso. The research employed a descriptive qualitative design, and data were collected through observation sheets, interviews, questionnaires, and documentation. The results indicated that teachers demonstrated good mastery of the material and conducted effective coaching during tutoring sessions. However, most teachers showed less creativity and innovation in motivating students. Despite this, tutoring had a positive impact on students’ learning motivation, as reflected in their persistent effort, resilience in facing difficulties, focus, academic performance, and independence in learning. The study concluded that the implementation of tutoring is positively related to enhancing students’ motivation and learning engagement.